Batasan Kewenangan Pengadilan Mengadili Praperadilan Berdasarkan Undang-Undang No. 20 Tahun 2025 Tentang Kitab Undang-Undang Hukum Acara Pidana (KUHAP) - Abdul Hayy Nasution (Bajang Institute, 2026)
The enactment of Law Number 20 of 2025 concerning the Criminal Procedure Code (KUHAP) brings significant changes to the regulation and authority of pretrial proceedings in Indonesia. This study aims to analyze the authority of Indonesian courts in adjudicating pretrial applications and the implementation of limitations on pretrial proceedings under Law Number 20 of 2025. This study uses a juridical-empirical approach with a descriptive research design. Data were obtained through document studies, interviews, and literature studies using primary and secondary legal materials. The findings show that the new KUHAP expands the objects and subjects of pretrial proceedings, including the examination of coercive measures, termination of investigations or prosecutions, compensation and rehabilitation, unrelated seizures, undue delay, and suspension or postponement of detention. The study also identifies limitations on repeated pretrial applications concerning the same coercive measure and restrictions on appeals against pretrial decisions. These provisions strengthen legal certainty, procedural efficiency, and the protection of human rights in the Indonesian criminal justice system